2018
DOI: 10.1111/tbed.12889
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of lumpy skin disease outbreaks in Russia in 2016

Abstract: In 2015, the lumpy skin disease virus spread throughout the Russian Federation. Following a modified stamping-out campaign, the disease re-emerged with a greater incidence across 16 regions of Southern and Central Russia. A total of 313 outbreaks were reported to OIE. The highest outbreak frequency was observed in the republics of Chechnya (108), Kalmykiya (57), and Ingushetiya (35). The disease cases predominantly occurred in June and July 2016, starting from May to December; however, no association between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 22 publications
4
79
2
2
Order By: Relevance
“…Several aspects of epidemiology of LSDV remain unclear including how the virus transmits so efficiently and rapidly in summer months. Analyses of LSDV outbreaks in Russia in 2016 indicate that the highest number of outbreaks was reported in warm months, June and July (Sprygin et al, ), which is consistent with vector‐borne transmission. However, different vectors could operate under diverse climatic conditions; therefore, it is important to look at which vectors are responsible for transmission in different geographic areas.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Several aspects of epidemiology of LSDV remain unclear including how the virus transmits so efficiently and rapidly in summer months. Analyses of LSDV outbreaks in Russia in 2016 indicate that the highest number of outbreaks was reported in warm months, June and July (Sprygin et al, ), which is consistent with vector‐borne transmission. However, different vectors could operate under diverse climatic conditions; therefore, it is important to look at which vectors are responsible for transmission in different geographic areas.…”
Section: Introductionmentioning
confidence: 77%
“…() indicated that in Israel, the abundance of S. calcitrans statistically correlates with the occurrence of LSDV; however, the true role for the stable fly in LSDV epidemiology still remains obscure (Chihota et al., ). In Russia, the stable fly occurs only in late July–early August (Aubakirov, ), but the outbreak began in early July, which also conflicts with the biological cycle of S. calcitrans in that region, as LSDV outbreaks may start appearing as early as spring (Sprygin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumpy skin disease (LSD) is an economically devastating viral disease at both the regional and the national levels (Molla, de Jong, Gari, & Frankena, ). It is a transboundary disease, that can spread beyond an outbreak area and reach epidemic proportions (Casal et al., ; Sprygin, Artyuchova, et al., 2018a). The economic losses associated with the forced slaughter of weak animals, treatment of secondary microbial infections, vaccination costs and trade restrictions place a heavy burden on farmers and impede economic growth in the affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Other possible mechanisms involving contaminated semen, shared water troughs, direct contact between infected and susceptible animals, intrauterine transmission, and via contaminated milk or skin lesions in the mother's udder and teats to a calf have also been suggested (Ali, Ali, Atta, & Cepica, ; Annandale, Holm, Ebersohn, & Venter, ; Rouby & Aboulsoud, ; Weiss, ). However, these modes cannot completely explain the speed at which outbreaks occur in the field and sweep across a wide area (Sprygin, Artyuchova, et al., 2018a; Mercier et al., ).…”
Section: Introductionmentioning
confidence: 99%